Endovascular Stroke Treatment and Risk of Intracranial Hemorrhage in Anticoagulated Patients. Issue 3 (March 2020) - Meinel, Thomas R.; Kniepert, Joachim U.; Seiffge, David J.; Gralla, Jan; Jung, Simon; Auer, Elias; Frey, Sebastién; Goeldlin, Martina; Mordasini, Pasquale; Mosimann, Pascal J.; Nogueira, Raul G.; Haussen, Diogo C.; et al.
Abstract : Background and Purpose—: We aimed to determine the safety and mortality after mechanical thrombectomy in patients taking vitamin K antagonists (VKAs) or direct oral anticoagulants (DOACs). Methods—: In a multicenter observational cohort study, we used multiple logistic regression analysis to evaluate associations of symptomatic intracranial hemorrhage (sICH) with VKA or DOAC prescription before thrombectomy as compared with no anticoagulation. The primary outcomes were the rate of sICH and all-cause mortality at 90 days, incorporating sensitivity analysis regarding confirmed therapeutic anticoagulation. Additionally, we performed a systematic review and meta-analysis of literature on this topic. Results—: Altogether, 1932 patients were included (VKA, n=222; DOAC, n=98; no anticoagulation, n=1612); median age, 74 years (interquartile range, 62–82); 49.6% women. VKA prescription was associated with increased odds for sICH and mortality (adjusted odds ratio [aOR], 2.55 [95% CI, 1.35–4.84] and 1.64 [95% CI, 1.09–2.47]) as compared with the control group, whereas no association with DOAC intake was observed (aOR, 0.98 [95% CI, 0.29–3.35] and 1.35 [95% CI, 0.72–2.53]). Sensitivity analyses considering only patients within the confirmed therapeutic anticoagulation range did not alter the findings. A study-level meta-analysis incorporating data from 7462 patients (855 VKAs, 318 DOACs, and 6289 controls) from 15 observational cohorts corroborated these observations, yielding an increased rate of sICH in VKA patients (aOR, 1.62 [95% CI, 1.22–2.17]) but not in DOAC patients (aOR, 1.03 [95% CI, 0.60–1.80]). Conclusions—: Patients taking VKA have an increased risk of sICH and mortality after mechanical thrombectomy. The lower risk of sICH associated with DOAC may also be noticeable in the acute setting. Improved selection might be advisable in VKA-treated patients. Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03496064. Systematic Review and Meta-Analysis: CRD42019127464. Abstract : Supplemental Digital Content is available in the text.